Legal Certainty Of Advocate Organizations Authorized To Carry Out The Appointment And Swearing-In Of Advocates - I Putu Merta Suadi; Made Subawa; Siti Nurmawa Damanik (PT Publikasiku Academic Solution, 2024)
Highlighting significant issues within the Indonesian legal system, particularly concerning the profession of advocates. After the enactment of Law Number 18 of 2003 concerning Advocates (the Advocate Law), the Indonesian Advocates Association (PERADI) was initially mandated as the sole organization authorized to appoint and swear in advocates. This was intended to create legal certainty and establish uniform standards for the legal profession. This situation has been complicated by varying court rulings, with some decisions recognizing the authority of organizations other than PERADI to appoint and swear in advocates, while others adhere to the Advocate Law, which exclusively grants this authority to PERADI. The diversity of court rulings reveals sharp differences in legal interpretation, leading to doubts about legal validity. This research aims to examine and analyze the legal certainty regarding which advocate organizations are authorized to carry out the appointment and swearing-in of advocates. The research employs a normative juridical approach. The findings suggest that any actions taken by advocate organizations other than PERADI, which appear to utilize one of the eight powers granted to PERADI by the Advocate Law, including proposing the Advocate Oath to the High Court, constitute unlawful acts that harm PERADI as the sole entity entitled to such authority. These actions can be subject to legal accountability in both criminal and civil domains. This research is expected to provide comprehensive recommendations for improving the advocate legal system in Indonesia.